Desarrollo de la inteligencia emocional basada en la empatía de los niños y niñas del Colegio Padre Ramón Arcila Ramírez (2021)
The present research aims to analyze how the process of emotion control occurs contributing to the development of emotional intelligence based on empathy of children from COPRAR school, identifying their emotional development, interpreting their relationship between peers and describing their behaviors based on social competences. The qualitative methodology was used to investigate phenomena with the purpose of understanding and knowing aspects of reality, information was obtained through tests, questionnaires and experiential workshops that allowed identifying different positions on the subject of emotional intelligence, a link was made with the narrative methodology because it intends to achieve that the work carried out takes into account different experiences taking into account each one of the points of view allowing the researcher teacher to question and make visible a problem in this case in the classroom. During the research process that was carried out in the Padre Ramon Arcila Ramirez School, it was possible to evidence that children in early childhood, and especially children from 5 to 6 years old, are very sensitive and empathic with others. This allowed the identification of this previous knowledge through the participant observation that was carried out in a virtual way through the experiential workshops, tests and family interviews, being this an essential process for the collection of information of this work